Analisis Isi Buku Ajar Bahasa Arab Terhadap Peningkatan Minat Belajar Bahasa Arab Siswa Kelas X Mas Ppm Al-Yusriyah - Muhammad Habib Azroi; Zulfahmi Lubis (LP. Ma'arif Janggan Magetan, 2023)
This research was conducted to analyze how the contents contained in Arabic Language Textbooks can affect the learning interest of MAS PPM-AL YUSRIYAH students in class X. In conducting this research, researchers applied qualitative research methods with data collection techniques used were interviews, documentation, distribution of questionnaires, and make direct observations. The results obtained in this research activity have shown that the Arabic language book has criteria that meet the requirements in terms of discussion and the content of the material in it is in line with the scientific foundation in which there are: the strength of the material provided, the security of the contents of the material, and supporting materials . If assessed based on the gradation, presentation, and selection of the textbook, it meets the required criteria and can be entered properly. The use of Arabic Textbooks has been proven to increase students' interest in learning Arabic. The material presented in detail coupled with the methods and ways of teaching the teacher in the classroom can add enthusiasm to student learning.